REEVALUATING C-SECTION TRENDS IN INDIA: UNDERSTANDING THECULTURAL AND CLINICAL FACTORS DRIVING CHANGE - Suresh Suvarna, Shruti (2025)
The rising rates of cesarean section (C-section) deliveries in India have become a subject of significant concern, driven by both cultural and clinical factors. This letter to the editor explores the multifaceted reasons behind the increasing preference for C-sections, including socioeconomic pressures, medicalization of childbirth, and patient perceptions of safety and convenience. It also examines the role of healthcare infrastructure, doctor-patient dynamics, and the growing influence of private healthcare systems in shaping delivery choices. By critically analyzing these factors, this letter aims to shed light on the need for a more balanced approach to childbirth, emphasizing patient education, informed consent, and the promotion of vaginal birth when medically appropriate.